Noodle processing, storage time and cooking affect the antioxidant activities and phenolic compounds content of Qingke barley noodles. (21st February 2020) - Tuersuntuoheti, Tuohetisayipu; Wang, Zhenhua; Duan, Mengjie; Asimi, Sailimuhan; Ren, Xin; Wang, Ziyuan; Zheng, Yanyan; Wu, Yan; Liang, Shan; Zhang, Min
Summary: The impact of noodle processing, storage and cooking on the total phenol content (TPC) and total flavonoid content (TFC) was assessed. Total phenol content (TPC) and total flavonoid content (TFC) of mixed flour were 77.50 and 39.56 mg per 100 g, respectively, and it decreased to 71.80 and 36.30 mg per 100 g after noodle processing. For the fresh Qingke barley noodles (FQBNs), stored at 25 °C, both TPC and TFC decreased significantly during storage. After cooking the fresh noodles, the TPC of the noodles stored for 0 and 4 h increased, while it decreased for the noodles stored for 8, 16 and 24 h; the TFC of all cooked Qingke barley noodles (CQBNs) decreased. Compared with the flour, the DPPH, ABTS +, HO and O 2 ∙ - scavenging ability and ferric reducing antioxidant power (FRAP) decreased significantly ( P <  0.05) after noodle processing. For FQBN, increased storage time led to a reduction in antioxidant ability. After cooking, the DPPH and HO scavenging ability and FRAP of noodles stored at 25 °C for 0 and 4 h, and the ABTS + and O 2 ∙ - scavenging ability of noodles stored at 25 °C for 0, 4 and 8 h increased. Overall, noodle processing, storage and cooking will affect the phenolic compound content and antioxidant activities of barley noodles. Although the shelf life of FQBN is 17 h at 25 °C, from the perspective of nutrition, it is not suitable for long‐term storage, and it is best choice to consume it within the first 4 h. Abstract : Total phenolic and flavonoids content and the antioxidant capacity of Wheat and Qingke barley mixed flour, uncooked Qingke barley fresh noodles stored at 25 °C for 0, 4, 8, 16 and 24 h, and the corresponding cooked Qingke barley noodles were determined.